Microleakage of Total-etch and Self-etch adhesives in class V composite cavities - Farzin Ebrahimi Sh; Shadman N; Molaie N (Tehran University of Medical Sciences, 2011)
"nBackground and Aims: This ex vivo study was done to evaluate the effect of different adhesive systems on microleakage of class V composite restorations."nMaterials and Methods: Thirty extracted human third molar teeth were selected and class V cavities were prepared (3×3×1.5 mm) on buccal and lingual surfaces. Then, teeth were divided into 3 groups. Adhesives used in this study were Excite (Ivoclar/Vivadent), AdheSE(Ivoclar/Vivadent) and AdheSE-one Ivoclar (Vivadent/Vivadent). After application of adhesives, cavities were restored with a resine composite (InTen-S A1/ Ivoclar), in 3 increments and cured with QTH light curing unit (700 mW/cm). After 24 hours storage of teeth in 370C water, teeth were thermocycled (500 cycles in 5-550C) and stored in 1% basic fushin for 24 hours. After that, the specimens were rinsed with running water and mounted in a self-cured acryl. Finally, the specimens were sectioned and maximum depth of dye penetration for each restoration was measured using stereomicroscopy. The results were statistically analyzed with Mann-Whitney U test."nResults: In comparison between enamel and dentin margins in each group, microleakage in enamel margins were less than that of dentin margins. This difference was statistically significant in Excite and AdheSE-one groups (P=0.001, P=0.043). AdheSE showed the least microleakage in dentin margins; however, there was no significant difference between 3 bonding agents (P=0.14). In enamel margins, there were significant differences between 3 bonding agents (P=0.001). Excite showed the lowest microleakage and AdheSE-one had the highest microleakage."nConclusion: The least enamel microleakage was associated with the total-etch and least dentin microleakage was observed in the two-step self-etch adhesive system.